1999
DOI: 10.1152/jn.1999.81.3.1045
|View full text |Cite
|
Sign up to set email alerts
|

Intersegmental Dynamics Are Controlled by Sequential Anticipatory, Error Correction, and Postural Mechanisms

Abstract: The purpose of this study is to examine the mechanisms underlying control of intersegmental dynamics during reaching movements. Two experiments were conducted to determine the relative contributions of anticipatory and somatosensory feedback mechanisms in controlling intersegmental dynamics and whether adaptation to novel intersegmental dynamics generalizes across a range of movement directions. The mechanisms used to control interaction torques were examined by altering the inertial load of the forearm. Movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
226
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(246 citation statements)
references
References 37 publications
(46 reference statements)
17
226
1
2
Order By: Relevance
“…It has been proposed that internal representations of limb dynamics within the CNS are used in the predictive compensation of forces arising from intersegmental dynamics (Beer et al 2000;Krakauer et al 1999;Sainburg and Kalakanis 2000;Sainburg et al 1993Sainburg et al , 1999Topka et al 1998). In a study of mechanisms underlying the control of interaction torques during reaching movements, Sainburg et al (1999) found that once subjects adapted to reaching with a load that altered their effective forearm inertia, they produced large errors in subsequent reaches to the same target with a new load configuration.…”
Section: Anticipatory Motor Compensation For Self-generated Interactimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that internal representations of limb dynamics within the CNS are used in the predictive compensation of forces arising from intersegmental dynamics (Beer et al 2000;Krakauer et al 1999;Sainburg and Kalakanis 2000;Sainburg et al 1993Sainburg et al , 1999Topka et al 1998). In a study of mechanisms underlying the control of interaction torques during reaching movements, Sainburg et al (1999) found that once subjects adapted to reaching with a load that altered their effective forearm inertia, they produced large errors in subsequent reaches to the same target with a new load configuration.…”
Section: Anticipatory Motor Compensation For Self-generated Interactimentioning
confidence: 99%
“…In a study of mechanisms underlying the control of interaction torques during reaching movements, Sainburg et al (1999) found that once subjects adapted to reaching with a load that altered their effective forearm inertia, they produced large errors in subsequent reaches to the same target with a new load configuration. Open-looped forward simulations using the muscle torques calculated from the adapted trials predicted the initial errors in movement direction.…”
Section: Anticipatory Motor Compensation For Self-generated Interactimentioning
confidence: 99%
“…Not all researchers use a model that includes an elaborate description of the intrinsic muscle properties (Sainburg et al 1999;Scheidt et al 2005;Shadmehr and Mussaivaldi 1994). This raises the question to what extent conclusions on motor control depend on the level of simplification with which the dynamics of the periphery are modeled.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest way to model the periphery is by neglecting all neural and muscle-tendon properties, resulting in a torque-driven model: motor commands prescribe directly the joint torques over time (e.g., Kawato 1990;Sainburg et al 1999). The simplest way to take into account the viscoelastic properties of the muscles and tendons is to describe the periphery as a second-order time-invariant linear massspring-damper system (e.g., Scheidt et al 2005;Shadmehr and Mussaivaldi 1994;Thoroughman and Shadmehr 1999).…”
Section: Introductionmentioning
confidence: 99%
“…14 Internal forces include those produced by "interaction forces" (i.e., interaction torques) imposed on each limb segment by motion of the segments attached to it. 14 It has been shown previously that shoulder and elbow torques are tightly coordinated in healthy planar reaching movements 15,16,17 and 3D arm movements 18 such that interaction torques are wellcompensated. 19 Failure of the nervous system to properly compensate for multi-joint interaction torques can lead to increased movement curvature and the desynchronization of motions at the shoulder and elbow joints.…”
Section: Introductionmentioning
confidence: 99%